Effect of Aloe vera Gel Formulation and Jatropha multifida L Leaf on the Growth of Staphylococcus aureus Bacteria - Dektra, I Made Putra Pramaditya; Pauzi, Iswari; Srigede, Lalu; Jiwintarum, Yunan (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Staphylococcus aureus bacteria is one of the agents of health problems that require special attention. Inappropriate use of antibiotics can cause resistance, so a more effective and safe alternative treatment is needed, one of which is by giving aloe vera gel formulations and tintir castor leaves that can help overcome bacterial infections, such as Staphylococcus aureus. Knowing the effect of aloe vera gel formulation (Aloe vera) and tintir castor leaf (Jatropha multifida) on the growth of Staphylococcus aureus bacteria. The study was pre-experimental with a cross sectional design. Gel formulations were made with various comparisons between aloe vera gel and tintir castor leaf, then tested against Staphylococcus aureus bacteria by observing the inhibition zone as an indicator of antibacterial activity. The results of testing the Aloe vera gel formulation and castor leaf filtrate showed that there was no inhibition zone in each of the tested formulation ratios. In the testing using Aloe vera gel formulations and Jatropha multifida leaf extract, no inhibition zones were observed in the 1:1 and 1:3 ratios, but an inhibition zone was present in the 3:1 ratio, measuring 4–6 mm with an average inhibition zone of 5 mm. This result can be considered sensitive but at a low level for inhibiting bacterial growth. There is an effect of Aloe vera gel and jarak tintir leaf formulation on the growth of Staphylococcus aureus bacteria.